A discussion paper on stigmatizing features of diabetes. Issue 2 (24th January 2018) - Abdoli, Samereh; Doosti Irani, Mehri; Hardy, Lynda R.; Funnell, Martha
Abstract: Aim: This manuscript aims to describe stigmatizing features of diabetes. Design: This article presents a narrative review of literature pertaining to stigma surrounding diabetes in different contexts. Methods: A literature search was conducted in CINAHL, PubMed and Web of Science for qualitative studies published between 2007–2017. The search was completed using various combinations of diabetes, T1DM, T2DM, stigma, social/public stigma, internalized/self‐stigma, stigmatization and diabetes‐related stigma in English. The reviewers then independently reviewed the eligible studies ( N = 18) to extract data. Results: From the 18 studies included in this narrative review, seven features related to stigma in diabetes were identified. People with diabetes were most notably considered and stigmatized as being "sick, " "death reminder, " "rejected marriage candidate, " "self‐inflicting, " "contagiousness, " "requiring a dietary modification" and "drunk or drug abuser."